A silicon nanocrystal/polymer nanocomposite as a down-conversion layer in organic and hybrid solar cells. Issue 27 (18th June 2015) - Svrcek, V.; Yamanari, T.; Mariotti, D.; Mitra, S.; Velusamy, T.; Matsubara, K.
Abstract : Demonstration of silicon nanocrystal down-conversion enhancement in PTB7:[70]PCBM based solar cells. Abstract : Silicon nanocrystal (Si-nc) down-conversion is demonstrated to enhance organic and hybrid organic/inorganic bulk heterojunction solar cells based on PTB7:[70]PCBM bulk heterojunction devices. Surfactant free surface-engineered Si-ncs can be integrated into the device architecture to be optically active and provide a means of effective down-conversion of blue photons (high energy photons below ∼450 nm) into red photons (above ∼680 nm) leading to 24% enhancement of the photocurrent under concentrated sunlight. We also demonstrate that the down-conversion effect under 1-sun is enhanced in the case of hybrid solar cells where engineered Si-ncs are also included in the active layer.